The family background of the anxiety-depressive disorder of 15 year old school boy - Masiak, Jolanta; Eugene, Andy (Current Problems of Psychiatry, 2011)
Abstract 15 years old school boy of the third year of secondary school is treating as an outpatient patient since seven years. The boy was born in the family of two parents and three years younger sister. Both parents have university education. The mother is been treated for several years as a psychiatric outpatient patient with the diagnosis of pervasive delusional disorder. On the other side she played important role in the family functioning. The father of the boy was rather passive and not involved as much as the mother in supporting their children. The younger sister, has been treated as an outpatient patient for three years for anxiety disorders. For the moment she is well and is doing well at school. In the 7th year ofage the boy has started complaining for anxiety symptoms and persecutory feelings and lack of the sense of security in his class, because of the possible aggressive behavior of the other boys in the school and in the neighborhood. He felt also frightened by the possible following aggression of Germany against Poland. All those symptoms influenced substantially his social functioning, particularly the functioning in his peer group and in the school. He expressed many reactions of anxiety and depressive type. In the following years the threat of Germans was gradually reduced but very important was threat of the aggression of the other boys. From time to time the boy refused leaving his home. The last two years has changed substantially the social situation of the boy because of his rapid physical growth. So that his present physical condition is equal as the growth and strength of adult man. It has modified his position in the peer group, so that his contact with the rival boys became less anxious but the new compensating reactions appeared with the focusing on one school boy that was particularly aggressive in former years. This accumulation of emotions and impulsiveness that became important element of his social functioning make more and more difficult the coping with the conflict situation. They reflect among others specific family situation, his mother lived for many years with the feeling of the constant threat from her colleagues in the work place. From the other side his personality traits that can be compared to the personality structure of epileptoidal personality. This type of the personality is at present not included into the list of abnormal personalities of DSM and ICD, but clinical practice gives us a lot of data supporting our convenience that it is personality structure that should be diagnosed among other abnormal personality structures.